PROFIL KEMAMPUAN UMUM (GENERIC COMPETENCIES) YANG DIPERLUKAN BAGI PENYULUH PERTANIAN (THE PROFILE OF GENERIC COMPETENCIES NEEDED BY AGRICULTURAL EXTENSION WORKERS (AEW'S)) - Arifin, Miftakhul (Jurnal Ilmu-Ilmu Pertanian, 2006)
This study aimed at revealing the Ideal Generic Competencies (IGC) needed by AEW's based on the expert judgement, document analysis, AEW's coordinators' observation and the AEW's experience. This study was exploratory in nature. The data were collected through interview, documentation, and questionnaire methods, and analysed using the descriptive technique and profile analysis. The result of the descriptive analysis are as the followings. The profile of generic competencies needed by AEW's according to the expert's judgement and the document analysis are shown at the rank of Language and communication, Planning and organizing activities, Scientific and technological understanding, Problem solving, Personal and interpersonal, Mathematics, and Cultural understanding. Six of those generic competencies are most important categories, but that Cultural understanding is important category. Language and communication, Planning and organizing activities, Scientific and Technological understanding, and Problem solving were validated in field. The result of the validation shows that four of the generic competencies are frequently experienced by persons or groups of AEW's. The result of the Discriminant Test shows that there is no significant difference between the results of the groups of AEW's experience in field. The result of Product-moment correlation shows that the most of AEW's population has used the generic competencies on high category. Based on the results, four generic competencies are ideally needed by AEW's. This implied that those four generic competencies are crucial for AEW's to do the job of an agricultural extension well, so that the competency standard, and the educational and training curriculum are deviced in relevance with them.